2017
DOI: 10.5433/1679-0359.2017v38n4p1785
|View full text |Cite
|
Sign up to set email alerts
|

Beet seed priming with growth regulators

Abstract: Seed priming is a technique used to induce metabolic germination processes. Use of growth regulators in seed priming may facilitate increments in physiological processes during seed germination. The objective of this study was to evaluate the effect of priming and growth regulators on beet seed germination. The treatments were cultivar type (Early Wonder, Itapuã and Maravilha) and seed priming technique, which included a control (unconditioned seed) standard hydropriming (water) and a conditioning with salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Sugar beet seed health and quality are crucial for adequate plant growth and they are strictly associated with the productive yield both in terms of quantity and quality of the crop [ 8 ]. Unfortunately, the productivity of sugar beet is often limited by heterogeneous germination in the field, probably due to the presence of inhibitory substances in the pericarp of the seed as well as pathogen attacks [ 9 , 10 ]. Moreover, about 35–40% of the sugar beet seeds need to be discarded before sowing in the field because they are defective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar beet seed health and quality are crucial for adequate plant growth and they are strictly associated with the productive yield both in terms of quantity and quality of the crop [ 8 ]. Unfortunately, the productivity of sugar beet is often limited by heterogeneous germination in the field, probably due to the presence of inhibitory substances in the pericarp of the seed as well as pathogen attacks [ 9 , 10 ]. Moreover, about 35–40% of the sugar beet seeds need to be discarded before sowing in the field because they are defective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, different techniques have been adopted in order to increase the physiological potential of sugar beet seeds and their treatment may become an indispensable procedure aiming at the enhancement of the seed vigor and the reduction of the variability in the germination process. Among these, seed priming with water, salicylic acid, or gibberellic acid has been shown to promote sugar beet seed germination as well as enhance sugar beet seedling growth [ 10 ]. Szajsner et al [ 14 ] showed that the seed vigor, germination speed, and the germination time significantly improved by using a magnetic field or a semiconductor laser radiation as pre-sowing treatments of sugar beet seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Seed quality is the basis of adequate plant establishment and is associated with the productive success of crops 1 . Therefore, a variety of strategies are employed in improving seed germination, seedling growth, and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of strategies are employed in improving seed germination, seedling growth, and productivity. Seed priming, a low-cost and low-risk tool, is considered to be the most effective of these methods 1 4 . It comprises a pre-sowing treatment of soaking seeds in a specified solution, allowing some metabolic activities to proceed before germination 5 , 6 , and can increase germination percentage, shorten germination time, and improve seedling establishment 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…vulgaris ). While the quality of the seeds is essential for proper plant growth and production [ 12 ], the productivity of sugar beet is often limited by the heterogeneity of germination in the field [ 13 , 14 ]. The results show that microalgae extracts can be used as a priming agent, as they increase the efficiency and regularity of the germination process of B. vulgaris seeds.…”
Section: Highlights Of the Special Issuementioning
confidence: 99%